Does fiscal decentralization affect regional disparities in health? Quasi-experimental evidence from Italy - Cinzia Di Novi; Massimiliano Piacenza; Silvana Robone; Gilberto Turati (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2019)
Recent theories on fiscal decentralization support the view that sub-national governments who finance a larger share of their spending with taxes raised locally by themselves are more accountable towards their citizens. Whilst evidence on improvements in spending efficiency is relatively common, little is known about the effects on inequalities amongst the population. In this paper we exploit a reform aimed at increasing regional tax autonomy in Italy to provide quasi-experimental evidence on the impact of fiscal decentralization on health disparities between- and within-regions. Our findings, robust to a number of robustness checks, support the view that fiscal decentralization does not impact on between-regional inequalities but can help to reduce inequalities within regions. However, this last effect depends on the degree of economic development: richer regions are better than poorer ones in containing inequalities.
Keywords: H75; I14; I15; I18; R50; 330; fiscal decentralization; regional governments; healthcare policy; health inequalities